Novel Pyrazolo[3,4-b] Pyridine Derivative (HLQ2g) Attenuates Hypoxic Pulmonary Hypertension via Restoring cGKI Expression and BMP Signaling Pathway - Li, Lijun; Yin, Minghui; Hu, Liqing; Tian, Xiaoting; He, Xiangrong; Zhao, Congke; Li, Ying; Li, Qianbin; Li, Xiaohui (Frontiers in Pharmacology, 2021)
Pulmonary hypertension (PH) is an extremely serious cardiopulmonary disease, finally leading to progressive right ventricular failure and death. Our previous studies have nominated HLQ2g, a pyrazolo[3,4-b] pyridine derivative stimulating soluble guanylate cyclase (sGC), as a new candidate for the treatment of PH, but the specific mechanism is still not clear. The PH model induced by hypoxia was established in rats. Right ventricular systolic pressure (RVSP) was assessed by jugular vein catheterization. RV weight was the index to evaluate RV hypertrophy. The protein levels of cGMP-dependent protein kinase type I (cGKI), bone morphogenetic protein receptor 2 (BMPR2), phosphorylated Smad1/5/8 (p-Smad1/5/8), and inhibitor of differention 1 (Id1) in pulmonary artery and human pulmonary artery smooth muscle cells (HPASMCs) were determined by western blotting. Cell proliferation and migration were evaluated. In the whole experiment, the first clinically available sGC stimulator Riociguat was used as reference. In hypoxic PH rat model, elevated RVSP and RV hypertrophy were significantly reduced by HLQ2g treatment. Both of Riociguat and HLQ2g attenuated vascular remodeling accompanied with up-regulated cGKI expression and BMP signaling pathway, which was characterized by elevated expression of BMPR2, p-Smad1/5/8 and Id1 in HPH rats. In addition, HLQ2g inhibited proliferation and migration of HPASMCs induced by hypoxia and platelet-derived growth factor (PDGF), restored BMPR2 signaling, which was recalled by Rp-8-Br-PET-cGMPS, the inhibitor of cGKI. In summary, the novel pyrazolo[3,4-b] pyridine derivative HLQ2g can alleviate HPH progression by up-regulating cGKI protein and BMP signaling pathway. Key words: Pulmonary hypertension; Hypoxia; cGKI; BMP signaling pathway; Pulmonary artery smooth muscle cells